Pengaruh Kualitas Produk, Kualitas Pelayanan, Dan Brand Image Terhadap Loyalitas Member PT. Natural Nusantara - Adiva Muallamatal Khikmah; Indra Krishernawan; Azizah Fitriani (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
This research is motivated by the decreasing number of member distributors of PT. Natural Nusantara Mojokerto Branch, it turns out that there are several factors causing member loyalty to decrease in 2021. This study aims to examine the effect of Product Quality (X1) Service Quality (X2) Brand Image (X3) on Member Loyalty (Y) distributor of PT. Natural Nusantara Mojokerto Branch. The sampling technique was carried out using a non-probability model with a purposive sampling method. The sample used in this study were 110 respondents from member distributors of PT. Natural Nusantara Branch Mojokerto, data collection techniques through a questionnaire with a Likert scale. The data analysis method used is multiple linear regression with validity test, reliability test, classical assumption test, and hypothesis testing. The results of the research conducted, partial regression test (t test) showed that Product Quality, Service Quality and Brand Image had a positive and significant influence on the Member Loyalty variable. Simultaneous regression test (Test F) shows that all the Independent Variables studied have a significant effect on Member Loyalty Dependent Variables.